Ensino remoto na pandemia e a atividade de leitura em plataformas digitais - Soares, Rícardi Marques (2023)
In this work, the focus is on reading texts on digital platforms: a study on remote teaching in a public school in Porto Velho - Rondônia, and the reading and understanding of texts on digital platforms conceived as social work is delimited by the thematic outline: a remote teaching resource in a public school in Porto Velho - Rondônia. This research seeks to answer the following question: what are the particularities of the work of reading texts on digital platforms proposed by the Escola Estadual de Ensino Fundamental e Médio Profª. Flora Calheiros Cotrin in Porto Velho – Rondônia, during the Covid-19 pandemic? As a general objective, we seek to investigate the particularities of the work of reading texts on digital platforms proposed by the Escola Estadual de Ensino Fundamental e Médio Profª. Flora Calheiros Cotrin in Porto Velho - Rondônia during the Covid-19 pandemic, in light of the conception of reading as social work. As specific objectives, we present the following: a) Reflect on the work of reading texts carried out at the Escola Estadual de Ensino Fundamental e Médio Profª. Flora Calheiros Cotrin in Porto Velho - Rondônia during the Covid-19 pandemic, in the light of the conception of reading as sociais work and b) Analyze the work of reading texts carried out in the context investigated during the pandemic in order to relate the conceptions of reading and of text mobilized in relation to the specificities of the digital medium. The relevance of the theme is due to the challenge faced by teachers in promoting reading competence, since the school is fundamental in the development of learning and the integral formation of students. During the pandemic, schools needed to adapt to remote teaching and use digital platforms, which brought challenges such as digital exclusion and the need to rethink pedagogical practices. The research is based on theoretical foundations coming from the main authors with international prominence, Beugrande (1981), in addition to national authors, such as Marcuschi (1983, 1996, 2002,2008; Kleiman (2004, 2013) and Koch (1984, 1997, 2008, 2014), who consider reading texts as social work, in addition to addressing reading on digital platforms and work in schools during the pandemic based on relevant legislation and studies. The methodology involves data collection through interviews and questionnaires applied to teachers and 6th-grade students at the school. The expected results of this research aim to benefit society, encouraging other teachers to explore the theme and contributing to the development of students' reading habits. The study is organized into four chapters, in addition to the introduction and final considerations, addressing theoretical aspects, the text on digital platforms, methodological procedures, and analysis of the collected data. By analyzing the responses of students and teachers in the light of the proposed principles of analysis, it is possible to observe valuable discoveries about the work of reading on digital platforms. The shift to remote learning due to the pandemic has brought both challenges and opportunities to enhance the digital educational approach. The voices of students and teachers highlighted creative strategies to encourage reading. Furthermore, the analysis of the concepts of reading and text in the digital environment showed a significant interconnection. The educators' narratives and the students' perceptions demonstrated how reading intertwines with online nuances, influencing and being influenced by technology. The research mapped the practice of reading on digital platforms during the pandemic, offering an understanding of the interactions between reading, education, and digital media in challenging times